2015
DOI: 10.7861/clinmedicine.15-3-312
|View full text |Cite|
|
Sign up to set email alerts
|

Survey on the attitudes of hospital doctors towards the terms ‘acopia’ and ‘social admission’ in clinical practice

Abstract: Letters not directly related to articles published in Clinical Medicine and presenting unpublished original data should be submitted for publication in this section. Clinical and scientifi c letters should not exceed 500 words and may include one table and up to fi ve references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This latter finding contrasts with a survey of physicians in Wales in which two-thirds (62.7%) considered patients labelled as “social admissions/acopia” were a burden on national health resources, with 44.8% of physicians admitted to feeling that these patients were a burden on their time. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter finding contrasts with a survey of physicians in Wales in which two-thirds (62.7%) considered patients labelled as “social admissions/acopia” were a burden on national health resources, with 44.8% of physicians admitted to feeling that these patients were a burden on their time. 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 A survey from Wales showed that 51.8% of hospital physicians consider that they frequently care for these patients, encountering them several times per week. 15 …”
mentioning
confidence: 99%
“…“Acopia” is a term that has emerged in medicine and multi-disciplinary professions in the past few decades. It is a term that means “unable to cope” and while commonly used (Curran and Chattopadhyay, 2015), there is no common understanding of what the term means. Kee and Rippengale (2008) suggest that individuals described as “problematic” or “not coping at home with daily life” – are likely to be identified as acopic.…”
Section: Understanding “Acopia” – a Disputed Diagnosismentioning
confidence: 99%
“…If as Kee and Rippengale (2008) and Curran and Chattopadhyay (2015) identify, “acopia” is solely or crudely an inability to cope with daily activities at home – the condition should disappear in hospital. As a hospital in-patient, support is available 24 h a day – and as the individual is not in the home environment they could reasonably be expected to have no signs of “acopia”.…”
Section: Understanding “Acopia” – a Disputed Diagnosismentioning
confidence: 99%
See 1 more Smart Citation